Give me that big time religion: Adrian Rogers as a builder in the Southern Baptist convention, at Bellevue Baptist Church, and with his radio ministry Love Worth Finding, 1972-2005 - Weaver, Graham M. (Kansas State University, 2017)
As pastor of Bellevue Baptist Church from 1972 to 2005 and three-time President of the Southern Baptist Convention (SBC) in 1979 and 1986-1988, Adrian Rogers (1931-2005) played an integral role in promoting inerrancy within the SBC. His actions not only moved the SBC in a more conservative direction, if not a fundamentalist one, but also shifted Southern Baptists, politically, in the direction of the Republican Party. However, Rogers’s role in the SBC went further than just politics. His involvement within the SBC, his leadership at Bellevue Baptist Church and its eventual move to Cordova, Tennessee, suggest that Rogers was actually a builder. Love Worth Finding (LWF), has preserved his legacy after his death in 2005. As a result, this thesis argues that Adrian Rogers was not only a preacher, popular grassroots organizer within the SBC, or evangelist, but also a builder. If it had not been for Rogers, the “architectural” blueprint for the SBC would never have become a reality. When Rogers became pastor of Bellevue Baptist Church, the church resided in midtown Memphis and had close to 9,000 members. By the time he retired in 2005, the church had 28,000 members and was located in Cordova, Tennessee. Finally, Rogers launched LWF in the midst of the televangelist scandals of the late 1980s. Not only did LWF survive the unseemly televangelist fallout, it continues to broadcast Rogers’s sermons today.
Keywords: Adrian Rogers; W. A. Criswell; Southern Baptists; Christianity; Love Worth Finding; Bellevue Baptist Church